EFFICIENT CONVERSION OF FURFURYL ALCOHOL TO ETHYL LEVULINATE AND FURFURYL ETHYL ETHER USING COPPER(II) TUNGSTATE CATALYSTS - Husni Wahyu Wijaya; Rima Prastianti Putri; Ubed Sonai Fahruddin Arrozi (Walisongo Journal of Chemistry, 2026)
Furfuryl alcohol (FFA), a biomass-derived platform compound widely used in polymer synthesis, has considerable potential as a precursor for producing furfuryl ethyl ether (FEE) and ethyl levulinate (EL), which are high-value industrial solvents and fuel additives. Their commercial production requires an active, stable, and inexpensive catalyst. In this study, CuWO₄ catalysts calcined at different temperatures (CuWO₄-TC, CuWO₄-350, CuWO₄-500, and CuWO₄-650) were synthesized and structurally characterized using powder XRD, FTIR, and SEM-EDX. The catalytic performance of these catalysts in FFA alcoholysis using ethanol as the hydrogen donor was systematically investigated, and the products were analyzed using GC-FID and GC-MS. Among the catalysts, CuWO₄-TC exhibited 100% FFA conversion and a 99% EL yield at 160°C for 6 h. The catalytic activity of CuWO₄-350 was significantly influenced by temperature and reaction time, with 100% FFA conversion, 2% FEE yield, and 98% EL yield achieved at 180°C for 6 h. These results demonstrate the high efficiency of CuWO₄ catalysts for the selective conversion of FFA, offering a promising route for sustainable biomass valorization.